2020
DOI: 10.1371/journal.pone.0234624
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Sclerosing Cholangitis (PSC) Wellbeing Study: Understanding psychological distress in those living with PSC and those who support them

Abstract: Peer Review History: PLOS recognizes the benefits of transparency in the peer review process; therefore, we enable the publication of all of the content of peer review and author responses alongside final, published articles. The editorial history of this article is available here:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Emotional distress can be exacerbated by anxiety about the idiopathic nature of the disease, lack of effective therapy, and elevated cancer risk. [104,105] Assessment of PSC symptoms is complex in patients with IBD, which itself causes symptoms such as abdominal pain and fatigue. [106] There is a growing interest in measuring PSC symptoms through patient-reported outcome measures (PROM).…”
Section: Symptomsmentioning
confidence: 99%
“…Emotional distress can be exacerbated by anxiety about the idiopathic nature of the disease, lack of effective therapy, and elevated cancer risk. [104,105] Assessment of PSC symptoms is complex in patients with IBD, which itself causes symptoms such as abdominal pain and fatigue. [106] There is a growing interest in measuring PSC symptoms through patient-reported outcome measures (PROM).…”
Section: Symptomsmentioning
confidence: 99%
“…People with PSC have a decreased quality of life and dealing with uncertainties about course of disease and risk of cancer can generate anxiety, depression and social isolation. 456,464 In this regard, patient support groups should play a key role. Patients with IBD should also be encouraged to contact the related support groups.…”
Section: How Can Wellbeing Of People With Psc Be Optimised?mentioning
confidence: 99%
“…We also observed that risk for SLE and PSC was associated with better mental health outcomes. Epidemiological studies have reported higher psychological distress in patients with SLE and PSC (61,(64)(65)(66)(67). However, in a study exploring the genetic correlation between immune and psychiatric related phenotypes using GWAS summary statistics, SLE was found to be significantly positively correlated only with Schizophrenia and no other psychiatric phenotypes (68).…”
Section: Discussionmentioning
confidence: 98%